Corporate choice and individual values: using accounting to align incentives - John Christensen (Business Research, 2019)
Corporate choice is expected to reflect rational behavior and yet there is much anecdotal evidence suggesting the opposite. Often the accounting system plays a major part in such stories. Aligning incentives has always been one of the main concerns of the accounting system. Accounting control has been discussed intensively as one of the purposes of the management accounting system. Furthermore, accounting for stewardship has been important to the financial accounting debate. Goal congruency issues are central to this discussion. In particular, conflicting interests have been transparent in the transfer pricing literature. The development of the transfer pricing literature is used to illustrate the development of how the accounting system is a vehicle to align incentives in the organization. In conclusion, it is argued that the accrual accounting system more generally serves the purpose of aligning incentives.
Keywords: 650; Individual rationality; Corporate choice; Transfer pricing; Accrual accounting; Organizational design; Decentralization